2022
DOI: 10.1021/acs.jafc.2c01335
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Antimicrobial Peptide Isolated from Moringa oleifera Seed Protein Hydrolysates and Its Membrane Damaging Effects on Staphylococcus aureus

Abstract: The present study sought to identify and characterize a novel antimicrobial peptide, named MOp2 from Moringa oleifera seed protein hydrolysates, and elucidate its potential antimicrobial effects on Staphylococcus aureus. MOp2, with the amino acid sequence of His−Val−Leu−Asp−Thr−Pro−Leu−Leu (HVLDTPLL), was characterized as a hydrophobic anionic AMP of the β-sheet structure. MOp2 exhibited negligible hemolytic activity at 2.0× MIC, suggesting its inhibitory effect on the growth of S. aureus (MIC: 2.204 mM). It m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 58 publications
0
7
1
Order By: Relevance
“…Few anionic AMPs have been reported. Zhao et al [37] reported that anionic AMP, HVLDTPLL, isolated from hydrolysates of Moringa oleifera seed proteins, displayed activity against S. Typhimurium CICC 21484 at 4.4 mM RVAPEEHPTL and FFTQATDLLSR, which were anionic AMPs derived from Maillard reaction products and inhibited the growth of Escherichia coli at approximately 17 and 15 mM, respectively [38]. These reported peptides showed less effective antimicrobial activity than the EYHp6 reported in our study.…”
Section: Antimicrobial Activitycontrasting
confidence: 51%
“…Few anionic AMPs have been reported. Zhao et al [37] reported that anionic AMP, HVLDTPLL, isolated from hydrolysates of Moringa oleifera seed proteins, displayed activity against S. Typhimurium CICC 21484 at 4.4 mM RVAPEEHPTL and FFTQATDLLSR, which were anionic AMPs derived from Maillard reaction products and inhibited the growth of Escherichia coli at approximately 17 and 15 mM, respectively [38]. These reported peptides showed less effective antimicrobial activity than the EYHp6 reported in our study.…”
Section: Antimicrobial Activitycontrasting
confidence: 51%
“…However, the degree of α-helix varied due to one different amino acid in the sequence. This difference of secondary structure may have an effect on the bacterial targeting specificity of AMPs . Furthermore, Figure S1 showed that the surface of the peptides was positively charged as predicted with a theoretical pI greater than 7.0 (Table ), attributed to arginine and lysine in the amino acid sequence.…”
Section: Resultsmentioning
confidence: 99%
“…This difference of secondary structure may have an effect on the bacterial targeting specificity of AMPs. 35 Furthermore, Figure S1 showed that the surface of the peptides was positively charged as predicted with a theoretical pI greater than 7.0 (Table 1), attributed to arginine and lysine in the amino acid sequence. Therein, KTR was predicted to have a higher positive charge than KTA due to the presence of more arginine residues, suggesting that KTR peptides are more inclined to bind to negatively charged cell membranes through electrostatic interactions.…”
Section: Design and Bioinformatics Analysis Of Ampsmentioning
confidence: 96%
See 1 more Smart Citation
“…The MIC value of VSDH against S . aureus was lower than that of peptide Mop2 (HVLDTPLL) from Moringa oleifera seed protein hydrolysate at 2.2 mM [ 34 ] and SP-1 (KLVDASHRLATGDVAVRA) from the protein hydrolysate of Spirulina platensis at 8.52 mM [ 35 ]. The peptide AVDRAV, from laba garlic, showed a more effective MIC value of 0.1 mM [ 21 ].…”
Section: Resultsmentioning
confidence: 99%